Mitostemness. Issue 8 (18th April 2018) - Cuyàs, Elisabet; Verdura, Sara; Folguera-Blasco, Núria; Bastidas-Velez, Cristian; Martin, Ángel G.; Alarcón, Tomás; Menendez, Javier A.
ABSTRACT: Unraveling the key mechanisms governing the retention versus loss of the cancer stem cell (CSC) state would open new therapeutic avenues to eradicate cancer. Mitochondria are increasingly recognized key drivers in the origin and development of CSC functional traits. We here propose the new term "mitostemness" to designate the mitochondria-dependent signaling functions that, evolutionary rooted in the bacterial origin of mitochondria, regulate the maintenance of CSC self-renewal and resistance to differentiation. Mitostemness traits, namely mitonuclear communication, mitoproteome components, and mitochondrial fission/fusion dynamics, can be therapeutically exploited to target the CSC state. We briefly review the pre-clinical evidence of action of investigational compounds on mitostemness traits and discuss ongoing strategies to accelerate the clinical translation of new mitostemness drugs. The recognition that the bacterial origin of present-day mitochondria can drive decision-making signaling phenomena may open up a new therapeutic dimension against life-threatening CSCs. New therapeutics aimed to target mitochondria not only as biochemical but also as biophysical and morpho-physiological hallmarks of CSC might certainly guide improvements to cancer treatment.